Impact of pneumonia and lung cancer on mortality of women with hypertension - Yuechun Shen; Zuojun Tian; Dongfeng Lu; Junyao Huang; Zuopeng Zhang; Xinchun Li; Jun Li (Scientific Reports, 2016)
Abstract Essential hypertension is one of the most severe women’s health problems. Modern life brings more chances of pulmonary diseases to human. The purpose of the study is to investigate weather pneumonia and lung cancer are associated with the mortality of women with hypertension in different age. A cross-sectional retrospective study was conducted in women with hypertension, who were admitted into our hospital in 2004–2013. 14219 women were enrolled and 68.8 ± 12.2 year old (y). Isolated hypertension was 14.7%. The age of death was 78.1 ± 9.8 y. The mortality was 4.4% for average and 0.2%, 1.1%, 2.4%, 4.8%, 10.4% and 15.8% in group age ≦49, 50–59, 60–69, 70–79, 80–89 and ≧90 y separately. This mortality increased with age was positively significantly correlated with the increased incidences of pneumonia (P < 0.05, r = 0.77). Pneumonia was a significant risk associated with the mortality in age 55–89 y (OR = 6.4–22.5; 95% CI = 3.06–51.12). While, lung cancer was the significant risk in 70–79 y. These observations indicate that pneumonia and lung cancer are significant risk factors associated with the mortality of certain age women with hypertension, and bring an alert that pneumonia and lung cancer should be prevented and treated intensively in modern life in order to reduce the mortality.